The Legal Liability of Directors in State-Owned Enterprises: An Analysis of Judicial Inconsistencies in the Application of the Business Judgment Rule Doctrine: Pertanggungjawaban Hukum Direksi Perusahaan Milik Pemerintah: Analisis Perbedaan Putusan Hakim dalam Penerapan Doktrin Business Judgment Rule - Art, Stanley Muljadi; Lie, Gunardi (Indonesian Journal of Law and Economics Review, 2025)
General Background: The application of the Business Judgment Rule (BJR) in Indonesia plays a crucial role in protecting directors from liability for business decisions that result in losses, provided such decisions are made in good faith and for corporate interests. Specific Background: In corruption cases involving directors of State-Owned Enterprises (SOEs), Indonesian courts show inconsistency in applying BJR, particularly when cases intersect with lex specialis provisions of the Anti-Corruption Law. Knowledge Gap: Existing studies have not comprehensively examined how judicial disparities affect legal certainty, protection, and the substantive realization of justice in corruption adjudication. Aims: This study analyzes the implementation of BJR in corruption cases, assesses the impact of judicial disparities on legal objectives, and identifies appropriate BJR application within the national legal framework. Results: Findings show that BJR is applied inconsistently—some cases acknowledge it as a valid protective doctrine, while others disregard it when corruption elements are proven under lex specialis rules. Novelty: This research bridges doctrinal analysis and case-based judicial evaluation to demonstrate how BJR interacts with principles of justice, legal certainty, and public benefit in corruption enforcement. Implications: The study highlights the need for clearer judicial guidelines to ensure consistent application of BJR without undermining the fight against corruption, thereby strengthening preventive legal protection and substantive justice. Highlights: Courts apply the Business Judgment Rule inconsistently in corruption cases. Lex specialis principles often override BJR protection when corruption elements are proven. Clearer judicial standards are needed to ensure fairness and legal certainty. Keywords: Business Judgment Rule, Corruption Law, Judicial Disparity, Soe Directors, Legal Certainty